CHEMISTRY OF FOOD PRODUCTS OF PLANT ORIGIN (World Bulletin of Social Sciences, 2024)
Food technology is a branch of practical science dealing with the study of food production methods. The modern food industry covers dozens of industries with unique technologies, equipment and equipment. The enterprises of these industries produce cereals, flour, cereals, animal feed, bread, pasta, confectionery, oils and fats, sugar, meat, milk, canned food, alcohol, beer and other food products necessary for human nutrition